Adsorption Studies of Antimony on Manganese Dioxide Using Radiometric Techniques - M.A. Rauf; M. Ikram; S.M. Hasany; S.M. Najam-ud-Din (Adsorption Science & Technology, 1994)
The efficiency of manganese dioxide as an adsorbent for the removal of antimony has been examined using radiometric techniques. The optimum conditions for maximum adsorption were investigated. The influence of equilibrium time, the nature and composition of the electrolytes, shaking time and the effect of foreign ions and other metal ions on the adsorption behaviour of antimony was also studied. On the basis of these data, Te IV can be easily removed from antimony using manganese dioxide as an adsorbent. The adsorption was also found to obey the Langmuir equation, the mean sorption energy of Sb on MnO 2 being 11.7 kJ/mol.